Partisipasi Masyarakat dalam Pembangunan Desa pada Program Gerbang Swara - WIDYA ROSA SIHITE; ZAKARIA ZAKARIA (Universitas Sumatera Utara, 2017)
Gerakan Pembangunan Swadaya Rakyat (People Governmental Development Movement) started since the Bupati Instruction in Serdang Bedagai regency. The directive Instruction Number 4 (2005) about the Gerakan Pembangunan Swadaya Rakyat (People's Movement of Governmental Development) (Gerbang Swara).With the instruction is expected there are synergies and targeted development in accordance with spatial planning based on community needs, and also increase community participation in development. Community engagement is central to expedite the development process. Without this, the development activities would not run properly. This study explains the low level of community participation in development. This study found there arefour causes of low participation. First, economic background. Second, the lack of property ownership society submission to the government. Third, the less the public response to the program Gerbang Swara; Fourth, lack of socialization.The study used the approach to political development. This study method is descriptive. Collecting data with depth interview. Analysis of data using qualitative analysis.Keywords: Public policy, Community Participation, political development.